A Difficult Patient Encounter: Using a Standardized Patient Scenario to Teach Medical Students to Treat Medication-Seeking Patients - J. Chase Findley; Dawnelle Schatte; Jim Power (Association of American Medical Colleges, 2017)
Introduction Substance dependence and the misuse of prescription narcotic medications have recently been a topic of increased national attention. Since this is both a difficult and increasingly important area for medical student training, we created an addition to our psychiatry clerkship curriculum to address this need using a standardized patient scenario. Methods Standardized patient scenarios are a useful instructional and assessment tool for providing medical students with exposure to specific clinical scenarios that could not be consistently and reliably encountered in clinical rotations. We present a standardized patient scenario designed to challenge psychiatry clerkship students with recognizing and managing substance use disorders in patients with a difficult interaction style and medication-seeking behavior. Our scenario is unique in its expectations of students to appropriately manage a difficult clinical interaction in which collaborative treatment planning and advanced communication skills are critical to treatment success. Results In a narrative analysis of student postencounter reflections on this experience, most students who provided feedback indicated that the encounter was valuable to their psychiatry clerkship education. Discussion The inclusion of this learning opportunity in our clerkship has added value by assessing students' interpersonal communication skills and clinical ability to evaluate and manage substance use disorders, as well as by instructing students to manage a common and difficult clinical scenario regardless of their future specialty choice.